Cultural Tourism in Indonesia: The Relevance of Policy to Accompanying Issues - Atika, Firdha Ayu; Pramono, Retno Widodo Dwi (Journal of Local Government Issues, 2026)
Cultural tourism is seen as effective in introducing cultural heritage and as a source of foreign exchange, but it also creates a dualism of meaning that can threaten cultural destruction. For this reason, appropriate policies are needed to optimize opportunities and anticipate threats. This research aims to find principles for optimizing cultural tourism policies related to developing issues, taking Indonesia as a case. The research method is bibliometric analysis and content analysis applied to scientific articles and official documents published by the government related to the development of cultural tourism. The variables observed are trends in the number of tourist destinations, visitors, foreign exchange earnings from the tourism industry, government policies, and emerging issues. The results indicate that cultural tourism development in Indonesia is characterized by a persistent dualism, where economic gains are accompanied by risks of cultural commodification and degradation. The findings show that existing policies demonstrate moderate responsiveness to tourism growth and emerging issues, but remain limited in ensuring equitable benefit distribution, controlling land-use change, and strengthening community empowerment. Furthermore, the study identifies that policy optimization is most effectively achieved through a holistic and collaborative governance approach that enables adaptive responses to the dualism inherent in cultural tourism development.